Assessment of Fungal Growth at Hemodialysis and Peritoneal Dialysis Unit in Hawler Teaching Hospital - Vian Al-Barzinji (College of Education for Pure Sciences, 2020)
Dialysis is used when the patient's kidneys can no longer perform their functions normally; it is a treatment that performs the functions of natural kidneys. Most patients begin dialysis when their kidneys have lost 85-90% of their ability to work naturally and they have to depend on dialysis for the rest of their lives, is called end -stage renal disease (ESRD). Infection in patients with end stage renal disease (ESRD) is usually treated with hemodialysis (HD) or peritoneal dialysis (PD). End stage renal disease a major cause of morbidity and mortality, in order to assess the fungal growth at hemodialysis and peritoneal dialysis unit a descriptive study was conducted at hemodialysis and peritoneal dialysis units in Hawler teaching hospital, from 15th of January to the end of May 2017;the study also includes the access sites and peritoneal catheter site. Factors that affected the access site among dialysis patient in the hospital. Sample of 63 patients, who were attending to the dialysis unit at time of the data collection, had been taken; in addition to that swab samples had been gathered from access site and peritoneal catheter site. The results of the study revealed that the fungal growth was positive at dialysis access sites, where the total percentage was 84.1% and that of peritoneal catheter site was 15.85%. In these unites, different types of filamentous fungi and yeasts had been successfully isolated.